An Analysis of the Orientation of Achievement of National Education Goals through the Merdeka Belajar Policy in Indonesia - Kemas Imron Rosadi; Anatun Nisa Mun'amah (CV. Zabags Qu Publish, 2023)
The purpose of this study is to provide an analysis of the implementation of the Merdeka Belajar policy, whether it has been running according to the achievement of the national education goals or not. This study is important as the basis for the direction of the implementation of education in Indonesia. The assessment process uses the library research method by collecting information in the form of journals, books, and literature according to the theme. Then, analyzed deductively and interpretively, resulting in a conclusion that the policy of Merdeka Belajar is perceived as an effort to create a learning environment that is free to express and free from various obstacles, especially psychological pressure. However, three things become obstacles in the orientation of the policy, including an understanding of the intent and implementation that is still lacking, neglected principles in education, and infrastructure inequality. Resulting in the national education goals cannot be fully achieved.